Panglima Laot's Persuasive Strategy in Assisting Law Enforcement Against Illegal Fishing Activities - Anhar Fazri*; Saiful Amri; Al Zuhri; Zuwidah Dewi; Ritayani Ritayani (Riwayat: Educational Journal of History and Humanities, 2023)
The sea is one area that is part of people's lives in Indonesia, especially in West Aceh Regency, Aceh Province. The wealth of the sea makes it a source of income for some people who have a profession as fishermen. However, the condition of the sea will not be separated from illegal fishing actions carried out by irresponsible parties, causing disruption of marine ecosystems and sources of public opinion. Therefore, it is necessary for the participation of various parties in protecting the marine area. This study aims to obtain a persuasive strategy of Pangilma Laot in increasing the participation of various parties to assist law enforcement in guarding illegal fishing activities. The research method used in this research is participatory action research which involves various parties involved to play an active role in the object of study in this research. The results of this study prove the need for the participation of various parties in supporting panglima laot for law enforcement to reduce the number of illegal fishing.